Stable Gastric Pentadecapeptide BPC 157 Therapy for Primary Abdominal Compartment Syndrome in Rats - Tepes, Marijan; Gojkovic, Slaven; Krezic, Ivan; Zizek, Helena; Vranes, Hrvoje; Madzar, Zrinko; Santak, Goran; Batelja, Lovorka; Milavic, Marija; Sikiric, Suncana; Kocman, Ivica; Simonji, Karol; et al. (Frontiers in Pharmacology, 2021)
Recently, the stable gastric pentadecapeptide BPC 157 was shown to counteract major vessel occlusion syndromes, i.e. peripheral and/or central occlusion, while activating particular collateral pathways. We induced abdominal compartment syndrome (intra-abdominal pressure in thiopental-anesthetized rats at 25 mmHg (60 min), 30 mmHg (30 min), 40 mmHg (30 min), 50 mmHg (15 min), and in esketamine-anesthetized rats (25 mm Hg for 120 min) as a model of multiple occlusion syndrome. By improving the function of the venous system with BPC 157, we reversed the chain of harmful events. Rats with intra-abdominal hypertension (grade III, grade IV) received BPC 157 (10 µg or 10 ng/kg sc) or saline (5 ml) after 10 min. BPC 157 administration recovered the azygos vein via the inferior-superior caval vein rescue pathway. Additionally, intracranial (superior sagittal sinus), portal and caval hypertension and aortal hypotension were reduced, as were the grossly congested stomach and major hemorrhagic lesions, brain swelling, venous and arterial thrombosis, congested inferior caval and superior mesenteric veins, and collapsed azygos vein; thus, the failed collateral pathway was fully recovered. Severe ECG disturbances (i.e., severe bradycardia, ST-elevation until asystole) were also reversed. Microscopically, transmural hyperemia of the gastrointestinal tract, intestinal mucosa villi reduction, crypt reduction with focal denudation of superficial epithelia, and large bowel dilatation were all inhibited. In the liver, BPC 157 reduced congestion and severe sinusoid enlargement. In the lung, a normal presentation was observed, with no alveolar membrane focal thickening, no lung congestion or edema, as well as absent severe intra-alveolar hemorrhage. Moreover, severe heart congestion, subendocardial infarction, renal hemorrhage, brain edema, hemorrhage, and neural damage were prevented. In conclusion, BPC 157 cured primary abdominal compartment syndrome.